(untitled) (Journal of Bio-Science, 2021)
The present study reports the morphological and molecular characterization of marine neogastropods collected from the South-East to the South-West coasts of Bangladesh. A total of 21 species under 13 families were identified morphologically, of which 7 species were barcoded successfully using partial sequence of mitochondrial cytochrome oxidase subunit-I (COI) gene. The average nucleotide frequencies of these species were G (guanine) = 20.57%, C (cytosine) = 18.44%, A (adenine) = 23.65%, T (thymine) = 37.35% and the GC content was 39.01%. The average Kimura two-parameter (K2P) distances of the COI barcode sequences within species, genera, and families were 20.7%, 22.0%, and 22.0%, respectively. The average inter-species genetic divergence was calculated as 21.0%. In addition, the COI barcode sequence of Nassarius stolatus was identified and submitted to the GenBank for the first time. The study also reports the new record of a species, Indothais rufotincta Tan & Sigurdsson, 1996 from Bangladesh. This finding greatly extends the distributional range of this species from the West coast to the East coast of the Bay of Bengal. J. Bio-Sci. 29(1): 79-91, 2021 (June)